Bulletin 85 Analyses of Mine and Car Samples of Coal Collected in the Fiscal Years 1911 to 1913 - Arno C. Fieldner (The National Institute for Occupational Safety and Health (NIOSH), 1914)
In connection with investigations relating to fuels belonging to or for the use of the United States Government, the causes of accidents in coal mines, the geologic relations of coal beds, and the character of the coal and the value of the fuel in the public lands, many mine samples of coal are analyzed each year in the laboratories of the Bureau of Mines. The systematic collection and analysis of coal samples in connection with investigations of fuels was begun in 1904 at the Government fuel-testing plant at the Louisiana Purchase Exposition, and was under the direction of the United States Geo- logical Survey for six years. Descriptions of the coal samples col- lected in connection with these investigations between the beginning of this work, July 1, 1904, and the transfer of the fuel-testing and mine-accident investigations to the Bureau of Mines, July 1, 1910, were compiled and published in Bureau of Mines Bulletin 22. The present bulletin presents analyses and descriptions of samples collected during the fiscal years 1911 to 1913. In order that the material in this bulletin may be used to supplement that presented in Bulletin 22, the same plan of geographical classification has been fol- lowed, the analyses and descriptions of the samples being grouped in alphabetical order according to the State, county, and town near which the mines or prospects sampled are situated.